Ki Hadjar Dewantara’s Leadership Trilogy for Technology-Integrated Learning: A Systematic Literature Review - Rahman, Sapta Isniar; Hariri, Hasan; Sari, Siti Rahma; Rusdiani, Atik (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
This study examines Ki Hadjar Dewantara’s leadership trilogy and its relevance to technology-integrated learning through a systematic literature review. The study aims to synthesize previous research findings and to develop a conceptual framework of pedagogical leadership based on Ki Hadjar Dewantara’s leadership philosophy in the context of digital learning environments. This research employed a systematic literature review method using the stages of identification, screening, eligibility, and inclusion. A total of 15 journal articles published between 2020 and 2025 were selected based on relevance to Ki Hadjar Dewantara’s leadership and educational practices. Data were analysed using content analysis and narrative synthesis by summarizing, comparing, and interpreting the findings of each study. The results indicate that the principles of Ing Ngarso Sung Tulodho, Ing Madya Mangun Karso, and Tut Wuri Handayani are consistently implemented in educational leadership practices through exemplary leadership, participatory leadership, and mentoring roles. The findings also show that these leadership principles are relevant to technology-integrated learning, particularly in the roles of teachers as learning designers, facilitators, and mentors in digital learning environments. This study conceptually reconstructs Ki Hadjar Dewantara’s leadership trilogy as a pedagogical leadership framework that integrates instructional design, digital pedagogy, and technology-integrated learning.